Increased risk of maternal and neonatal complications in hormone replacement therapy cycles in frozen embryo transfer - Liping Zong; Peihao Liu; Liguang Zhou; Daimin Wei; Lingling Ding; Yingying Qin (BMC, 2020)
Abstract Background The endometrial preparation during frozen embryo transfer (FET) can be performed by natural cycle (NC), hormone replacement therapy (HRT) cycle and cycle with ovulation induction (OI). Whether different FET preparation protocols can affect maternal and neonatal outcomes is still inconclusive. Methods This was a retrospective cohort study that included 6886 women who delivered singleton live birth babies after 28 weeks of pregnancy underwent FET from January, 2015 to July, 2018. Women were divided into three groups according to the protocols used for endometrial preparation during FET: NC group (N = 4727), HRT group (N = 1642) and OI group (N = 517). Results After adjusting for the effect of age, body mass index (BMI), irregular menstruation, antral follicle count (AFC), endometrial thickness, the levels of testosterone, anti-Müllerian hormone (AMH), preconceptional fasting glucose (PFG), systolic and diastolic pressure et al., the HRT group had higher risk of hypertensive disorders of pregnancy (HDP) compared with the NC group (adjusted odds ratio (aOR) 2.00, 95% confidence interval (CI) 1.54-2.60). Singletons born after HRT FET were at increased risk of low birth weight (LBW) compared to NC group (aOR 1.49, 95%CI 1.09-2.06). The risks of preterm birth (PTB) in the HRT and OI group were elevated compared with the NC group (aOR 1.78, 95%CI 1.39-2.28 and aOR 1.51, 95%CI 1.02-2.23, respectively). Conclusions The HRT protocol for endometrial preparation during frozen embryo transfer of blastocysts was associated with increased risk of maternal and neonatal complications, compared to the NC and OI protocol.